Апериодические и колебательные процессы разряда конденсатора при принудительном ограничении длительности токов в нагрузке - Щерба, А.А.; Супруновская, Н.И.; Синицин, В.К; Иващенко, Д.С. (Технічна електродинаміка, 2012)
The transient processes of oscillatory and aperiodic discharge of storage capacitors on load with forced limitation of pulse current duration in it using switching off of fully controllable semiconductor switch are studied. In order to increase average pulse power of discharge pulses in circuits of its semiconductor formers it is proposed to increase a capacitance of capacitors discharged on load.